Recognition of brain activities via graph-based long short-term memory-convolutional neural network - Yang, Yanling; Zhao, Helong; Hao, Zezhou; Shi, Cheng; Zhou, Liang; Yao, Xufeng (Frontiers in Neuroscience, 2025)
IntroductionHuman brain activities are always difficult to recognize due to its diversity and susceptibility to disturbance. With its unique capability of measuring brain activities, magnetoencephalography (MEG), as a high temporal and spatial resolution neuroimaging technique, has been used to identify multi-task brain activities. Accurately and robustly classifying motor imagery (MI) and cognitive imagery (CI) from MEG signals is a significant challenge in the field of brain-computer interface (BCI).MethodsIn this study, a graph-based long short-term memory-convolutional neural network (GLCNet) is proposed to classify the brain activities in MI and CI tasks. It was characterized by implementing three modules of graph convolutional network (GCN), spatial convolution and long short-term memory (LSTM) to effectively extract time-frequency-spatial features simultaneously. For performance evaluation, our method was compared with six benchmark algorithms of FBCSP, FBCNet, EEGNet, DeepConvNets, Shallow ConvNet and MEGNet on two public datasets of MEG-BCI and BCI competition IV dataset 3.ResultsThe results demonstrated that the proposed GLCNet outperformed other models with the average accuracies of 78.65% and 65.8% for two classification and four classification on the MEG-BCI dataset, respectively.DiscussionIt was concluded that the GLCNet enhanced the model’s adaptability in handling individual variability with robust performance. This would contribute to the exploration of brain activates in neuroscience.